“NEW PERIPHERY STRATEGY” OF ISRAEL - Y. I. Kostenko (Vestnik MGIMO-Universiteta, 2017)
Israel’s strategy of the “periphery Doctrine” served as a way to enhance security and economic ties and reduce isolation. Following the deterioration of the regional situation Israel had begun to consolidate new relations with peripheral nations. The post-Arab Spring regional order has largely transformed the Central Asia-Israel potential partnership. New regional order has jeopardized Israel’s geostrategic balance, and so that country is looking to deepen alliances in the Muslim world. Central Asian states can fill that role. The basis for this partnership is the understanding by the involved parties that they share certain security and economic interests that can provide benefits. The relationships between Israel and Central Asian countries are long-established and cordial in the political, economic and strategic realms, and based on shared views of world order and intense person-to-person relations. All of the Central Asian governments cultivated their secular traditions and stepped up their anti-Islamic stance for fear of the development of domestic, Islamic-oriented opposition. Islam has no specific legal status in any of the five states in the region, and the fight against alleged Islamic extremism has become a mainstay of domestic and foreign policies. This article surveys the constellation of bilateral ties that has formed between Israel and the Muslim states of Central Asia and draws a comparison to Israel’s previous relations with peripheral countries Turkey and Iran. Person-to-person relations between Israel and Central Asia are probably Tel-Aviv’s leading means of influence in the region. Israeli investments have strengthened the political partnership.